A rapid approach for ecological assessments in Carolina Bay wetlands that were previously converted to agriculture - Moritz, Christopher M.; Vepraskas, Michael J.; Ricker, Matthew C. (Frontiers in Forests and Global Change, 2023)
Restoring wetlands is expensive, and methods for evaluating restoration condition are needed. This study developed chronosequences for use in ecological assessments (EAs) of restoration projects for Carolina Bay wetlands (CBWs) in the Southeastern US that were previously used for agriculture. An empirical method was also developed to estimate saturation levels to be used with the chronosequences. Data were collected from nine restored CBWs whose restoration ages ranged from 0 to 23 years. Plots were sorted into four Hydrologic Groups: 0–13 (Group 1), 14–50 (Group 2), 51–100 (Group 3), and 101+ (Group 4) consecutive days of saturation within 30 cm of the soil surface during the growing season. Litter thickness, tree basal area, and potential tree height were measured within a variable radius plot using a 10-factor prism across all Hydrologic Groups. Litter thickness and tree height reached an equilibrium at 15 years since restoration once crown closure occurred at the sites. In Groups 1 and 2, tree basal area reached an equilibrium at 15 years, and in Groups 3 and 4 it increased linearly to 23 and 21 years. Regression equations were developed (R2 = 0.57–0.73) to estimate saturation duration based on hydrology indicators, litter thickness, potential tree height, and soil type. These results showed that chronosequences and saturation duration would be useful for proposing performance standards in restored CBWs at time periods ranging from 5 to 23 years.